AN EVALUATION OF JOURNALISTS’ WORKING EFFECTIVENESS: THE ROLE OF DATA JOURNALISM AND JOURNALISM EXPERIENCES - İlknur Aydoğdu Karaaslan and Baha Ahmet Yılmaz and Tuğba Yiğit (Fonseca, Journal of Communication, 2025)
The world has witnessed technological changes and transformations, with the penetration of new concepts and ideologies. Journalism has also rapidly adapted to these changes and is responding to the needs of the age with new journalistic practices. This study aims to evaluate the impact of data journalism on journalism experiences and its role in achieving journalist working effectiveness. It also examines the moderating role of institutional support between journalism experience and journalists’ working effectiveness. By making use of a quantitative, descriptive research design and adopting a random sampling design, this study collected data from 290 media employees in Turkey. A questionnaire was designed based on validated scales, and findings were analyzed using smart-PLS software. The findings suggest that data journalism has a positive impact on journalism experiences, which in turn makes a positive impact on journalists’ working effectiveness. The results also show that institutional support positively moderates the relationship between journalism experiences and journalist working effectiveness. The study implications include suggestions on how to improve the journalists’ working effectiveness. It also recommends that newspaper companies must focus on data journalism and train their employees to contribute to employees’ journalism experience.